2016
DOI: 10.1118/1.4962928
|View full text |Cite
|
Sign up to set email alerts
|

Classification of breast lesions using segmented quantitative ultrasound maps of homodyned K distribution parameters

Abstract: The study showed that the analysis of internal changes in lesion parametric maps leads to a better classification of breast tumors. The authors recommend combining multiple features for characterization, instead of using only one parameter, especially in the case of heterogeneous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…For each mass, two perpendicular scans were recorded. The OASBUD was originally used to assess the statistical properties of backscattered ultrasound echoes in breast tissue and to differentiate breast masses using transfer learning with CNNs . Detailed descriptions of both datasets can be found in the original papers …”
Section: Methodsmentioning
confidence: 99%
“…For each mass, two perpendicular scans were recorded. The OASBUD was originally used to assess the statistical properties of backscattered ultrasound echoes in breast tissue and to differentiate breast masses using transfer learning with CNNs . Detailed descriptions of both datasets can be found in the original papers …”
Section: Methodsmentioning
confidence: 99%
“…Examples of methods of quantitative analysis of raw ultrasonic signals have been described in detail by several authors in previous papers . Here, we provide two simple Matlab data‐processing examples which may help other users to manipulate the data.…”
Section: Data Format and Usage Notesmentioning
confidence: 99%
“…The OASBUD were previously used by our group to assess the statistical properties of ultrasound echoes and differentiate breast lesions. We have shown that the use of the homodyned K distribution may be helpful in differentiation of lesion type, and that using the combination of the Nakagami distribution and the BI‐RADS may improve the specificity of traditional ultrasonic examination …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the most reliable diagnostic results were obtained for liver and renal tissues lesions, because their normal, healthy structures are nearly homogeneous. The classification of the strongly heterogeneous breast tissue is however still an open issue (Byra et al, 2016). Recent study revealed that the medium contraction and expansion induced by a temperature change results in relative displacement of the scatterers in heated tissue.…”
Section: Introductionmentioning
confidence: 99%